A Review of Personality-Targeted Interventions for Prevention of Substance Misuse and Related Harm in Community Samples of Adolescents - Edalati, Hanie; Conrod, Patricia J. (Frontiers in Psychiatry, 2019)
Several school-based prevention programmes have been developed and used to prevent, delay, or reduce substance misuse and related problems among community samples of adolescents. However, findings indicate that many of these interventions are associated with null, small, or mixed effects in reducing adolescent substance misuse, in particular for those mostly at risk of transitioning to substance use disorders. These findings highlight the need to shift the focus of substance use prevention efforts toward intervention strategies which directly target high-risk adolescents. The Preventure programme was designed to target four personality risk factors for substance misuse: hopelessness, anxiety sensitivity, impulsivity, and sensation seeking. This article reviews findings from the previous trials of personality-targeted interventions (i.e., Preventure programme) with adolescents and discuss the promises and benefits of these interventions for targeting community samples of high-risk adolescents at school level for reducing substance misuse and related mental health problems. Findings indicated that this programme has been successful in reducing the rates of alcohol and illicit drug use and substance-related harms by approximately 50% in high-risk adolescents with the effects last for up to three years. These interventions were also associated with a 25% reduction in likelihood of transitioning to mental health problems, such as anxiety, depression, suicidal ideation, and conduct problems. The programme is particularly beneficial for youth with more significant risk profiles, such as youth reporting clinically significant levels of externalizing problems, and victimised adolescents. A key strength of the Preventure programme is that it is embedded in the community and provides substance use intervention at school level to the general samples of high-risk adolescents who might not otherwise have access to those programmes.